PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS AUGMENTED REALITY (AR) PADA GURU MGMP MATEMATIKA SMP KOTA BUKITTINGGI - Suherman, Defri Ahmad, Nurul Afifah Rusyda (Departemen Matematika, 2020)
Mathematics learning requires concrete evidence and examples in its implementation. This is often an obstacle experienced by teachers with a lack of mathematics learning media. This can lead to low student interest in mathematics. One of the materials that requires learning media in mathematics is geometry. However, the teacher's lack of ability to apply technology in mathematics learning hampers the learning process. One of the efforts that can be done is through community service aimed at SMP Mathematics teachers who are members of the Mathematics MGMP for SMP Kota Bukittingi. This training activity is structured in two stages, namely designing and building AR applications using Unity3D. This activity is carried out online which begins with providing an understanding of augmented reality technology, the modeling process using the Blender application, making markers and the Vuforia SDK to form AR and playmaker as programming, and the final stage is to create applications using unity software. Every stage of the activity is monitored and evaluated so that the activity is carried out properly. Based on the results of the service activities that have been carried out, it is concluded that the digital props based on Augmented Reality have been successfully created and help learning of geometry materialKunci: Mathematics learning, Augmented Reality, learning of geometry material.